Analysis of the Management of Facilities and Infrastructure at the South Sulawesi Province Office of Communication, Informatics, Statistics, and Encryption - Fadillah, Nur; Jamaluddin, Jamaluddin; Isgunandar, Isgunandar (Pendidikan Administrasi Perkantoran, UNM, 2025)
This study aims to analyze the management of facilities and infrastructure at the Diskominfo-SP Office of South Sulawesi Province, as well as identify the supporting and inhibiting factors involved in this management. This study uses a qualitative approach with a descriptive research type that focuses on the management of facilities and infrastructure based on procurement, storage, maintenance, and inventory indicators. The data collection techniques used are observation, interviews, and documentation. The study's results indicate that the management of facilities and infrastructure at the Communication, Informatics, Statistics, and Encryption Office of South Sulawesi Province is considered